(untitled) (Prostor, 2024)
The research is focused on interdisciplinary approaches in the field of urban planning, architecture, and design in organized housing construction. Eight hypothetical models are proposed based on four criteria: interdisciplinarity, authorship, rationalization, and social sustainability. The research evaluated the technical heritage of the models and proposed a hypothetical future model for settlement planning in organized residential construction.